Porphyromonas gingivalis in the Oral Cavity of English Bulldog Newborn Puppies - Martini, Andresa de Cássia; Gomes, Lianna Ghisi; Pitchenin, Letícia Camara; Pizzinatto, Fábio Dumit; Sônego, Dábila de Araújo; Almeida, Emanuelle Denise de Brito; Spiller, Paulo Roberto; Costa, Murilo de Souza Mendes da; Nakazato, Luciano; Souza, Roberto Lopes de (Acta Scientiae Veterinariae, 2017)
Background: Periodontal disease (PD) is the most common disease of the oral cavity in cats and dogs, and it affects up to 80% of these animals. PD begins with the accumulation of bacteria on the surface of the teeth, and it poses a risk for the health of pets. Research on PD in dogs has focused on the identification and characterization of bacterial communities present in the oral cavity. Porphyromonas gingivalis is highly prevalent in the oral cavity. Therefore, the aim of this study was to detect P. gingivalis before and after dental eruption in 15 English bulldog newborn puppies, hoping to contribute to early guidance of oral hygiene management and prevent future PD. Materials, Methods & Results: Fifteen English bulldog newborn puppies were used in this study. Two groups (G1 and G2) were formed with eight and seven puppies, respectively. Oral swab samples were taken from the maxillary incisor region of animals from G1 and G2 10 days after birth (T10). At this moment, the clinical evaluation of the oral cavity showed healthy gums with a thin, shiny, pinkish, and firm margin, without any odor or granular appearance, and with no tooth eruption. On postnatal day 25 (T25), a subgingival sample was collected with a Gracey curette from the maxillary incisors; the oral cavity examination revealed healthy gums and presence of gingival sulcus. Bilateral subgingival samples were also collected from the maxillary canines and fourth premolars of the dams at T10 and T25. All newborn puppies were fed maternal breast milk and supplementation exclusively with commercial milk for dogs in individual bottles. The dams were fed commercial dry food. The average weight of G1 and G2 at T10 was 625.87 ± 85.26 g and 543.50 ± 92.88 g, respectively, and 100% (15/15) of the animals were negative for PG as assessed by polymerase chain reaction (PCR) on oral swab samples. At T25, puppies from groups G1 and G2 weighed 1.465 ± 194 g and 1.206 ± 201 g, respectively, and 100% (15/15) of the puppies were positive for P. gingivalis as assessed by PCR on subgingival samples collected with a Gracey curette. The dams of the puppies in G1 and G2 were positive for PG at T10 and T25 as determined by PCR on subgingival samples. Discussion:An important finding of this study was that the dams of the puppies in G1 and G2 were positive for P. gingivalis at T10. Several species of bacteria that cause periodontal disease can be transmitted from humans to pets; therefore, transmission from dam to puppy would be possible, but was not observed in this study at T10, when 100% (15/15) of the animals were negative for P. gingivalis. Subgingival microbiota associated with periodontitis consists essentially of Porphyromonas spp., and the presence of gingival sulcus and dental eruption are determinant factors for the presence of P. gingivalis in the oral cavity. Nevertheless, the hygiene habits of dogs, with the dam licking the puppies after dental eruption, could have been a relevant factor for transmission and appearance of P. gingivalis in the subgingival sample in 100% (15/15) of the puppies at T25. The oral microbiota is closely related to many diseases, and resident pathogenic oral bacteria can be transferred by close contact. Certain species of bacteria present in the subgingival biofilm exhibit higher etiologic relevance during the onset and progression of periodontitis, and Porphyromonas spp. is among the most important of these species. It is important to keep in mind that age is a relevant factor to prevent periodontitis. Therefore, providing owners with instructions for thorough dental brushing of animals when they still have deciduous teeth can prevent the appearance of future PD.